Analisis Net Plant Heat Rate (Nphr) Pembangkit Listrik Tenaga Uap Tanjung Enim 3x10 MW - Saripudin, Rian (Motor Bakar : Jurnal Teknik Mesin, 2025)
Net Plant Heat Rate (NPHR) is a parameter that shows the performance of a plant used to produce electrical power supplied by the plant. Net Plant Heat Rate (NPHR) is a value that describes the amount of energy used to produce electrical energy by the generator, the lower the Net Plant Heat Rate (NPHR) value, the higher the efficiency of a plant. Based on these problems, it is necessary to analyze the Heat Rate at the PLTU to find out whether it is in accordance with the specifications and to monitor the age capability of a plant, where the older the age of a plant, the performance decreases. The purpose of this research is to analyze the Net Plant Heat Rate of the generating system, analyze the factors that affect the Net Plant Heat Rate of the generating system, and make improvements to improve the performance of the generating system. This research method is to use the direct method by taking data on the High Heating Value (HHV) of coal, coal mass, generator power and electricity consumption power itself. The results of this study indicate the performance value of the Tanjung Enim 3x10 MW PLTU in good generating efficiency conditions with an NPHR value of 4,959 kcal/kWh.